Increasing running step rate reduces patellofemoral joint forces - Lehnhart, R. L.; Thelen, D. G.; Wille, C. M.; Chumanov, E. S.; Heiderscheit, B. C. (Medicine & Science in Sports & Exercise, 2014)
Purpose: Increasing step rate has been shown to elicit changes in joint kinematics and kinetics during running, and it has been suggested as a possible rehabilitation strategy for runners with patellofemoral pain. The purpose of this study was to determine how altering step rate affects internal muscle forces and patellofemoral joint loads, and then to determine what kinematic and kinetic factors best predict changes in joint loading.